Penguatan Rantai Nilai Pariwisata Sebagai Strategi Pengembangan Kawasan Kota Tua Jakarta Menjadi Kawasan Wisata Ramah Muslim - Ari Ana Fatmawati; Sugeng Santoso (Universitas Mercu Buana, 2020)
In order to make Indonesia the center of the world's Islamic economy, tourism is one of the potential sektors to be developed. The Ministry of Tourism and Creative Economy visited Indonesia as many as 6 million visitors until 2024. Kota Tua area is one of the priority tours that will be made Muslim-friendly tourism in DKI Jakarta. The purpose of this study is to provide recommendations for strategies in increasing visits to Kota Tua by 2000 visits / day where descriptive analysis is used as a research method (FGD, Deep Interview, Literature Study). The Tourism Value Chain (Accommodation, Food and Beverage and Tourism Assets) is based on the Standard Business Field Classification (KBLI) so that it becomes a reference in developing Muslim-friendly tourism activities. Recommended strategies used from the accommodation sektor are Rebranding conventional hotels to halal / Sharia hotels, especially three-star hotels, accelerating halal hotel certification, synergies with the Islamic capital sektor, synergies with Islamic boarding schools, and synergies with creative fields of Architecture / Interior Design. From the food and beverage sektor, it is proposed that the acceleration of halal certification, changes to healthy and halal food brands, and promotion by selecting a culinary ambassador to introduce local food. From the tourism asset sektor, Digital Tourism is one of the leading strategies, arranging museum collections, door-to-door promotions, increasing the intensity of performances held at museums, and increasing museum service programs as an institution that serves the community